Enfermedad de Addison en el niño. Reporte de un caso. - Amaro Méndez, Sergio; Beyra Alemañy, Manuel; Molina Sánchez, María Elena (Revista Cubana de Pediatría, 2023)
Primer caso que se presenta en este medio.